2020
DOI: 10.4067/s0717-95022020000200423
|View full text |Cite
|
Sign up to set email alerts
|

3-D Airway Analysis Related to Facial Morphology

Abstract: The aim of this investigation was to define the volume and area of the airway in subjects with Class II and Class III skeletal deformity. A cross-sectional study was designed including subjects with facial deformity defined by Steiner's analysis in subjects with indication of orthognathic surgery who presented diagnosis by cone beam computerised tomography. We determined the measurements of maximum area, minimum area and volume of the airway. The data were compared using Spearman's test, with statistical signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…However, the association between nasal septum deviation and facial asymmetries has been reported (Hafezi et al, 2010), This may lead to a hypothesis associated with the impact of nasal septum deformity and facial deformities. Previous studies have shown that subjects with a class III skeletal deformity have a higher airway volume than other subjects (Ravelo et al, 2020); however, information regarding the nasal apparatus is limited. The aim of this study was to identify septal deviations and changes in the inferior nasal concha bone in subjects with a class III facial deformity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between nasal septum deviation and facial asymmetries has been reported (Hafezi et al, 2010), This may lead to a hypothesis associated with the impact of nasal septum deformity and facial deformities. Previous studies have shown that subjects with a class III skeletal deformity have a higher airway volume than other subjects (Ravelo et al, 2020); however, information regarding the nasal apparatus is limited. The aim of this study was to identify septal deviations and changes in the inferior nasal concha bone in subjects with a class III facial deformity.…”
Section: Introductionmentioning
confidence: 99%
“…The maxillo-mandibular structures are modified by the development and growth in three dimensions and can be related to anatomical changes, such as the volume and shape of the airway [ 1 ]. Changes in the middle and lower third of the face with clockwise or counterclockwise rotation of the mandible are related to the position of the hyoid bone, the morphology of the facial thirds and the pharyngeal spaces [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…La cirugía ortognática se incluye dentro de los protocolos internacionalmente validados para el manejo de la apnea del sueño (Liu et al, 2019); estudios previos de nuestro grupo han determinado que la morfología de la VA se vincula a la morfología facial (Ravelo et al 2020) de forma que la modificación de la estructura implica cambios en la vía aérea; de la misma forma, se ha observado que los métodos de análisis y estudios de la VA no son relacionados con los métodos cefalométricos (Ravelo et al 2021a), instalando algunas dudas respecto de la forma de medir y diagnosticar las condiciones de vía aérea.…”
Section: Introductionunclassified
“…Es claro que sujetos con deformidades faciales de clase II presentan un reducido volumen de la VA y que sujetos con deformidad facial de clase III presentan en su mayoría un amplio volumen de vía aérea (Ravelo et al, 2020); se ha señalado también que, actualmente, la cirugía ortognática presenta una clara tendencia hacia el avance facial (Ravelo et al, 2021b), lo cual debe mejorar condiciones de la VA; sin embargo, en casos de retroceso mandibular la vía aérea puede reducirse lo cual puede ser complejo en casos de patología del sueño. El objetivo de este trabajo fue identificar el cambio de la VA generado en sujetos sometidos a cirugía ortognática bimaxilar.…”
Section: Introductionunclassified